Need Analysis and Context to Develop Motion Dynamics E-Student Worksheet Integrated Problem Solving Model to Improve Student’s Problem Solving Skills - Siti Aisyah Lubis; Selma Riyasni; Hidayati Hidayati; Renol Afrizon (Universitas Negeri Padang, 2026)
This research is driven by the limited problem-solving abilities of students in motion dynamics and the inadequate integration of digital learning resources that support such skills. The urgency of this study lies in the increasing demand for 21st-century learning that emphasizes problem-solving skills, critical thinking, and the integration of digital technology in physics education. However, current instructional materials used in schools are still largely conventional and have not effectively facilitated structured problem-solving processes. Therefore, this study aims to examine the needs and contextual basis for developing a problem-solving-oriented electronic student worksheet to foster students’ problem-solving competence. A qualitative descriptive method was employed, involving needs analysis through observations and questionnaires distributed to both students and teachers. The findings indicated that students required more interactive learning materials, real-life problem contexts, and guided problem-solving stages to better understand physics concepts. Teachers also expressed the need for practical digital resources that are easy to implement in classroom instruction and capable of supporting independent learning. These results provide an empirical foundation for the development of an electronic worksheet that aligns with curriculum objectives, learner characteristics, and technology-enhanced learning environments, while promoting active engagement and meaningful conceptual understanding for students across different levels of prior knowledge.